2022
DOI: 10.3389/fonc.2022.920990
|View full text |Cite
|
Sign up to set email alerts
|

Renal Abscess Caused by Crizotinib: A Rare Case Report

Abstract: Crizotinib is a tyrosine kinase inhibitor that has been found to be effective in the treatment of c-ros oncogene 1-positive non-small cell lung cancer. Although this targeted agent for treating cancer has shown superiority to standard chemotherapy in some ways, this drug has adverse effects, such as the development of renal abscesses. Some associated renal damage may disappear with crizotinib withdrawal. Hence, we present the case of a 58-year-old man with non-small cell lung cancer on crizotinib therapy who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…While pathogenetic mechanism of autosomal dominant polycystic kidney disease (ADPKD) might be different from that of CARC, it has been reported that hepatocyte growth factor (HGF) and its receptor, c-MET, to be involved in the formation of ADPKD [ 26 , 27 ]. In this regard, crizotinib is a dual c-MET and ALK inhibitor [ 10 , 15 17 ], but accumulating number of case reports demonstrated that crizotinib is associated with development of cystic lesions in the kidneys, liver, and pancreas [ 20 , 24 , 28 – 35 ]. While the mechanism of CARC formation remains to be defined, as proposed by Wiest et al [ 30 ], complete collection of the following information from the advanced NSCLC patients treated with crizotinib is recommended, that is, patient’s general information including age, gender, race/ethnicity, history of renal cysts; clinical information of primary including stage at diagnosis, genetic information, treatment history, treatment response, PFS; tyrosine kinase inhibitor-associated renal cysts including time to diagnosis, laterality, pathology, symptoms, complications, abnormalities in vitals and labs.…”
Section: Discussionmentioning
confidence: 99%
“…While pathogenetic mechanism of autosomal dominant polycystic kidney disease (ADPKD) might be different from that of CARC, it has been reported that hepatocyte growth factor (HGF) and its receptor, c-MET, to be involved in the formation of ADPKD [ 26 , 27 ]. In this regard, crizotinib is a dual c-MET and ALK inhibitor [ 10 , 15 17 ], but accumulating number of case reports demonstrated that crizotinib is associated with development of cystic lesions in the kidneys, liver, and pancreas [ 20 , 24 , 28 – 35 ]. While the mechanism of CARC formation remains to be defined, as proposed by Wiest et al [ 30 ], complete collection of the following information from the advanced NSCLC patients treated with crizotinib is recommended, that is, patient’s general information including age, gender, race/ethnicity, history of renal cysts; clinical information of primary including stage at diagnosis, genetic information, treatment history, treatment response, PFS; tyrosine kinase inhibitor-associated renal cysts including time to diagnosis, laterality, pathology, symptoms, complications, abnormalities in vitals and labs.…”
Section: Discussionmentioning
confidence: 99%